Inside the consulting room of a highly effective therapist: An analysis of first sessions. - Caçador, Sílvia; Sousa, Daniel; Cooper, Mick (Counselling & Psychotherapy Research, 2024)
Aim: The aim of this study was to capture the most salient aspects of first‐session activities by a therapist who consistently had good clinical outcomes. Method: Constructivist grounded theory was used to analyse the first three audio‐recorded psychotherapy sessions with two clients. Results: The analysis generated 12 categories organised into three major domains: (a) promoting clients' sense of agency and the collaborative nature of the therapeutic process; (b) supporting clients' exploration of meaningful contents, balancing responsively between following clients and introducing new dimensions; and (c) creating a climate of emotional security based on empathic presence, authenticity and positive regard. Conclusions: The results show key aspects of the therapist's performance, such as distinguished clinical skills, responsiveness and strong relational abilities. The results support the literature on highly effective therapists. They also contribute to practice and psychotherapist training. Domains and categories from this study may be the basis for a checklist of some essential features to be included in psychotherapists' deliberated practice programmes.